2011
DOI: 10.1002/pola.24694
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic block glycopolymers via atom transfer radical polymerization: Synthesis, self‐assembly and biomolecular recognition

Abstract: In this work the synthesis of poly(butyl acrylate)‐b‐poly(2‐{[(D‐glucosamin‐2‐N‐yl)carbonyl]oxy}ethyl methacrylate) (PBA‐b‐PHEMAGl) diblock glycopolymer and poly(2‐{[(D‐glucosamin‐2‐N‐yl)carbonyl]oxy}ethyl methacrylate)‐b‐poly(butyl acrylate)‐b‐poly(2‐{[(D‐glucosamin‐2‐N‐yl)carbonyl]oxy}ethyl methacrylate) (PHEMAGl‐b‐PBA‐b‐PHEMAGl) was performed via atom transfer radical polymerization. Monofunctional and difunctional poly(butyl acrylate) macroinitiators were used to synthesize the well‐defined diblock and tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The monofunctional and difunctional macroinitiators of poly( n ‐butyl acrylate), PBA‐Br ( M n , SEC =8200 g/mol; M w / M n =1.16) and Br‐PBA‐Br ( M n , SEC =11,600 g/mol; M w / M n =1.16), respectively, were synthesized via atom transfer radical polymerization (ATRP) as previously reported 29, 54, 55. The amphiphilic di‐ and triblock glycopolymers were synthesized via chain extension reaction of HEAGl from PBA macroinitiators.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The monofunctional and difunctional macroinitiators of poly( n ‐butyl acrylate), PBA‐Br ( M n , SEC =8200 g/mol; M w / M n =1.16) and Br‐PBA‐Br ( M n , SEC =11,600 g/mol; M w / M n =1.16), respectively, were synthesized via atom transfer radical polymerization (ATRP) as previously reported 29, 54, 55. The amphiphilic di‐ and triblock glycopolymers were synthesized via chain extension reaction of HEAGl from PBA macroinitiators.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly and mimicking the Nature, a variety of glycopolymers has been synthesized for different applications in biomedicine and biomaterials as tools for investigating carbohydrate‐based interactions, therapeutics and drug delivery systems 5, 7–10. This kind of polymeric material is prepared by different approaches:8, 11–14 (i) conventional2, 15–18 or controlled17, 19–31 polymerization techniques using protected or unprotected glycomonomers; (ii) chemical post‐modification using “classical”32–39 or “click” chemistry21, 40–44 methodologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the fact that many of the currently known CRDs only bind to the terminal oligosaccharides of glycans, glycopolymers with repeating pendent units show their great advantage in mimicking these terminal oligosaccharides [9][10][11][12], which is important to further exploration on both of the known and unknown carbohydrate-protein interactions. Meanwhile, the artificial glycopolymers and glyco-nanoparticles have show enhancement multivalent binding behavior of carbohydrate and lectins [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Leon et al [138,139] reported the synthesis of amphiphilic block glycopolymers derived from D-glucosamide methacrylate M63. According to one strategy (Entry 121-124, Table 2), M63 was homopolymerized using a monofunctional (A1) or a bifunctional initiator (A27) at 40 and 50 °C respectively (DMF, CuBr(L3)).…”
Section: (Meth)acrylate Monomersmentioning
confidence: 99%